The Association between Sibship Composition and Maternal Feeding Behaviors - Mosli, Rana (Progress in Nutrition, 2021)
Objective: To examine the association between sibship composition and maternal feeding behaviors. Method: A total of 309 Saudi mothers of children aged 3 to 5 years old were recruited. The study questionnaire, comprising of the previously validated Child Feeding Questionnaire-Arabic (CFQ-A) and questions assessing sibship composition and sociodemographic characteristics, was completed over the telephone. Descriptive and bivariate analyses, and multiple linear regression adjusting for covariates were performed. Results: We found a negative association between number of siblings (b: -0.11, 95% CI: -0.15, 0.01), number of older siblings (b: -0.15, 95% CI: -0.13, -0.02), and number of older sisters (b: -0.17, 95% CI: -0.29, -0.05) and perceived responsibility. There was a negative association between number of siblings (b: -0.16, CI: -0.16, -0.03), number of older siblings (b: -0.14, 95% CI: -0.12, -0.02), and number of older sisters (b: -0.21, 95% CI: -0.29, -0.09) and monitoring. Increase in number of siblings was associated with higher concern about child’s weight (b: 0.17, 95% CI: 0.01, 0.23) and higher concern about child’s diet (b: 0.14, 95% CI: 0.02, 0.23). Conclusion: Children who have more siblings, specifically older siblings and older sisters may experience unique maternal feeding behaviors that have been previously linked to poor dietary patterns, as mothers may share feeding responsibilities with older siblings/sisters. Further research is needed to identify the association between sibship composition and dietary habits/intake. Educating older siblings and older sisters on healthy eating may help them become positive reinforcers of a healthy lifestyle for younger siblings.